Too Much of a Good Thing? An Evolutionary Theory to Explain the Role of Ceramides in NAFLD - Poss, Annelise M.; Summers, Scott A. (Frontiers in Endocrinology, 2020)
Non-alcoholic fatty liver disease (NAFLD), which ranges from the relatively benign and reversible fatty liver (NAFL) to the more advanced and deadly steatohepatitis (NASH), affects a remarkably high percentage of adults in the population. Depending upon severity, NAFLD can increase one's risk for diabetes, cardiovascular disease, and hepatocellular carcinoma. Though the dominant histological feature of all forms of the disease is the accumulation of liver triglycerides, these molecules are likely not pathogenic, but rather serve to protect the liver from the damaging consequences of overnutrition. We propose herein that the less abundant ceramides, through evolutionarily-conserved actions intended to help organisms adapt to nutrient excess, drive the cellular events that define NAFL/NASH. In early stages of the disease process, they promote lipid uptake and storage, whilst inhibiting utilization of glucose. In later stages, they stimulate hepatocyte apoptosis and fibrosis. In rodents, blocking ceramide synthesis ameliorates all stages of NAFLD. In humans, serum and liver ceramides correlate with the severity of NAFLD and its comorbidities diabetes and heart disease. These studies identify key roles for ceramides in these hepatic manifestations of the metabolic syndrome.